The Effect of Financial Performance on Stock Prices in Food and Beverage Sub Sector Companies Registered in Indonesia Stock Exchange - Erin Hartutik (J-CEKI : Jurnal Cendekia Ilmiah, 2023)
Indonesia's growing economic conditions are expected to provide favorable prospects in meeting the needs of the community. The selection of this object is due to the growth of the food and beverage industry has increased. The Association of Food and Beverage Entrepreneurs (GAPMMI) estimates that the growth of the food and beverage industry specifically in the third quarter of 2022 is recorded to be quite high at 9 %, the accumulated growth of the food and beverage industry from January 2022 to the end of November 2022 is still higher than the overall industry growth which only 4% (cnnindonesia.com). This type of research is causal associative research. The researcher intends to examine the effect of variable current ratio (CR), debt to equity ratio (DER), net profit margin (NPM) on stock prices. The sampling technique in this study was purposive sampling with a total sample of 11 companies in the 2020-2022 period. The data obtained were analyzed with the help of SPSS software version 25.00 for windows. Based on the calculation, it is known that the calculated F value of 7.797 with a significance of F of 0.000 <0.05. The significance value of F is smaller than the predetermined significant level that is 0.05. So it can be concluded that all the independent variables together have a significant effect on the dependent variable. Current ratio (CR), debt to equity ratio (DER), and net profit nargin (NPM) variables together have a significant effect on stock prices on food and beverage companies listed on the IDX.